Joint association of vitamin D deficiency and sleep disorders with cardiovascular mortality: a prospective cohort study - Wang, Shizhen; Zheng, Dahong; Wang, Hui; Wu, Mengru; Xia, Wangjie; Luo, Zhen; Tian, Li (Frontiers in Nutrition, 2025)
PurposeVitamin D deficiency and sleep disorders may independently contribute to increased mortality, but the combined effects of these two factors on mortality remain unknown. This study aimed to investigate both the separate and joint effects of vitamin D deficiency and sleep disorders on cardiovascular disease mortality, as well as all-cause mortality and cancer mortality.MethodsWe analyzed data from 24,566 adults in the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2018. Sleep disorders were assessed using self-report questionnaires, and vitamin D levels were measured through serum total 25-hydroxyvitamin D [25(OH)D]. Cox proportional hazards models were employed to evaluate the associations between separate and joint effects of vitamin D deficiency and sleep disorders with mortality outcomes.ResultsOver a median follow-up of 9.08 years, we included a total of 24,566 individuals, in this study. Among them, 2,776 cases were all-cause deaths, 858 were cardiovascular disease deaths, and 644 were cancer deaths. We found that Vitamin D deficiency was independently associated with an increased risk of all-cause mortality, while sleep disorders were similarly associated with a higher risk of all-cause mortality. Notably, participants with both vitamin D deficiency and sleep disorders exhibited a significantly higher risk of all-cause mortality (HR, 2.31; 95% CI: 1.36–3.91) and cardiovascular mortality (HR, 2.39; 95% CI, 1.03–5.58) compared to those with only one or neither risk factor, even after adjusting for potential confounders.ConclusionOur study highlights that the combination of vitamin D deficiency and sleep disorders was associated with an increased risk of all-cause and cardiovascular mortality in adults. These findings might help to refine dietary and lifestyle intervention strategies for this population.